Seismic vulnerability assessment of the rail transport capability of a long-span cable-stayed bridge. (February 2023) - Duan, Jiahong; Deng, Kailai; Zhao, Canhui; Zhu, Hao; Huang, Can; Chen, Shanqin
Abstract: The operational states of long-span railway cable-stayed bridges are highly susceptible to changes resulting from earthquakes, which may disturb the normal passage of trains. To assess the seismic fragility of the rail transport capability of a long-span cable-stayed bridge, this study extends the applicable scope of the seismic vulnerability assessment from the structural behavior to the transport capacity. A numerical model of a benchmark bridge, the Baijusi Bridge, is developed using ABAQUS, and the modeling strategy is verified via a comparison with physical test results. An incremental dynamic analysis is performed to obtain the seismic responses of the Baijusi Bridge, and four damage levels are defined based on the mapping relationship between the permitted train speed and six smoothness indices. A fragility curve of each smoothness index is generated both for the most unfavorable value during an earthquake and for the residual value following an earthquake. The influence of the different smoothness indices on the vulnerability of the rail transport capability is then discussed. The results reveal that the acceptable train speed decreases even if structural damage does not occur. The influence law of the structural response on the rail transport capacity is then further discussed.